Comparison of Thrombolysis in Myocardial Infarction Score and Heart Score in risk stratification of acute myocardial infarction patients, prognostic accuracy and arrhythmia incidence - Batyala, Keerthana; Nagabhushana, M. V.; Dorasanamma, Malli (International Journal of Research in Medical Sciences, 2019)
Background: To compare TIMI & HEART SCORE for their risk stratification in Acute Myocardial Infarction Patients, prognostic accuracy and Arrhythmia incidence. Methods: This observational study is conducted in a Tertiary care hospital over a period of 2 years from August 2017 to July 2019. A total of 100 patients presented to ER with Chest Pain are selected for study. Patients were monitored for a period of one month in ICCU. Results: In present study out of 61 cases with TIMI score ≥5, mortality of 11.5%(7 cases, p value 0.028). Heart score more than 6 constitutes high risk group, out of which mortality was observed in 7.45% cases (p=0.48). Most of the arrhythmias (70.49%) in present study observed in patients with TIMI score ≥5 (High risk group) which is statistically significant with p value 0.002. Most of the arrhythmias in present study observed in patients with HS ≥8 which is not statistically significant with p value 0.135. Conclusions: In present study, overall mortality rate was 7% and these patients who died constitutes to high risk group with TIMI. HEART SCORE identified more patients as low risk compared to TIMI SCORE. TIMI SCORE is a good predictor of arrhythmia incidence.